Immunoglobulin Genomics in the Guinea Pig (Cavia porcellus) - Guo, Yongchen; Bao, Yonghua; Meng, Qingwen; Hu, Xiaoxiang; Meng, Qingyong; Ren, Liming; Li, Ning; Zhao, Yaofeng (PLOS ONE, 2012)
In science, the guinea pig is known as one of the gold standards for modeling human disease. It is especially important as a molecular and cellular biology model for studying the human immune system, as its immunological genes are more similar to human genes than are those of mice. The utility of the guinea pig as a model organism can be further enhanced by further characterization of the genes encoding components of the immune system. Here, we report the genomic organization of the guinea pig immunoglobulin (Ig) heavy and light chain genes. The guinea pig IgH locus is located in genomic scaffolds 54 and 75, and spans approximately 6,480 kb. 507 VH segments (94 potentially functional genes and 413 pseudogenes), 41 DH segments, six JH segments, four constant region genes (μ, γ, ε, and α), and one reverse δ remnant fragment were identified within the two scaffolds. Many VH pseudogenes were found within the guinea pig, and likely constituted a potential donor pool for gene conversion during evolution. The Igκ locus mapped to a 4,029 kb region of scaffold 37 and 24 is composed of 349 Vκ (111 potentially functional genes and 238 pseudogenes), three Jκ and one Cκ genes. The Igλ locus spans 1,642 kb in scaffold 4 and consists of 142 Vλ (58 potentially functional genes and 84 pseudogenes) and 11 Jλ -Cλ clusters. Phylogenetic analysis suggested the guinea pig’s large germline VH gene segments appear to form limited gene families. Therefore, this species may generate antibody diversity via a gene conversion-like mechanism associated with its pseudogene reserves.